A Bioprinted In Vitro Model for Osteoblast to Osteocyte Transformation by Changing Mechanical Properties of the ECM. Issue 10 (21st August 2019) - Lee, Bryan E. J.; Shahin‐Shamsabadi, Alireza; Wong, Michael K.; Raha, Sandeep; Selvaganapathy, Ponnambalam Ravi; Grandfield, Kathryn
Abstract: Osteocytes are key contributors to bone remodeling. During the remodeling process, trapped osteoblasts undergo a phenotypic change to become osteocytes. The specific mechanisms by which osteocytes work are still debatable and models that exist to study them are sparse. This work presents an in vitro, bioprinted model based on the previously developed technique, ExCeL, in which a cell‐embedded hydrogel is printed and immediately crosslinked using paper as a crosslinker‐storing substrate. This process mimics the phenotypical change of osteoblast to osteocyte by altering the mechanical properties of the hydrogel. By printing Saos‐2, osteosarcoma cells, embedded in the alginate hydrogel with differing mechanical properties, their morphology, protein, and gene expression can be changed from osteoblast‐like to osteocyte‐like. The stiffer gel is 30 times stiffer and results in significantly smaller cells with reduced alkaline phosphatase activity and expression of osteoblast‐marker genes such as MMP9 and TIMP2. There is no change in viability between cells despite encapsulation in gels with different mechanical properties. The results show that the phenomenon of osteoblasts becoming encapsulated during the bone remodeling process can be replicated using the ExCeL bioprinting technique. This model has potential for studying how osteocytes can interact with external mechanical stimuli or drugs. Abstract : An in vitro bioprinted model, based on the previously developed technique ExCeL, is used to mimic the encapsulation of osteoblast‐like cells and their subsequent phenotypical change to osteocyte‐like cells in gels of varying stiffness. Cells are viable in both gels despite a 30 times difference in stiffness. The stiffer gels induce morphological, protein, and gene expression changes consistent with osteocytes.